CSR Program-Occupational Health and Safety (K3) awareness among Laboratory Workers and Researchers at the School of Engineering, Telkom University - Wan Norlinda Roshana, Mohd Nawi (UMPSA, 2025)
BANDUNG, 13 August 2025 - Occupational Health and Safety Training – a CSR initiative for lab workers and researchers at Telkom University - learn directly from senior lecturers of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), which was successfully conducted on 13 August 2025 at Telkom University, Bandung, Indonesia.